2020
DOI: 10.1038/s41598-020-66432-9
|View full text |Cite
|
Sign up to set email alerts
|

Detecting quadrupole: a hidden source of magnetic anisotropy for Manganese alloys

Abstract: Mn-based alloys exhibit unique properties in the spintronics materials possessing perpendicular magnetic anisotropy (PMA) beyond the Fe and Co-based alloys. It is desired to figure out the quantum physics of PMA inherent to Mn-based alloys, which have never been reported. Here, the origin of PMA in ferrimagnetic Mn3− δ Ga ordered alloys is investigated to resolve antiparallel-coupled Mn sites using x-ray magnetic circular and linear dichroism (XMCD/XMLD) and a first-principles calculation. We found that the co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…However, the anisotropy direction of transition metal and rare earth based spin pumping are coupled to the crystal field anisotropy direction and orbital moment direction, respectively [36]. Furthermore, the hyperfine-interaction-induced quadrupole anisotropy (of the neglected term) may contribute to the observed large magnetic anisotropy of manganese alloys [37].…”
Section: Anisotropic Hyperfine Interaction Between Nuclear and Conduction Spinmentioning
confidence: 99%
“…However, the anisotropy direction of transition metal and rare earth based spin pumping are coupled to the crystal field anisotropy direction and orbital moment direction, respectively [36]. Furthermore, the hyperfine-interaction-induced quadrupole anisotropy (of the neglected term) may contribute to the observed large magnetic anisotropy of manganese alloys [37].…”
Section: Anisotropic Hyperfine Interaction Between Nuclear and Conduction Spinmentioning
confidence: 99%
“…20,27) Recently, Okabayashi et al revealed that orbital magnetic moments and anisotropies for Mn 3 Ga are low by combining the X-ray magnetic circular/linear dichroism (XMCD/XMLD) and theoretical calculations, whereas there is a band mixing between the Mn-3d up-and down-spin states, resulting a significant MA. 28) Because the MnAlGe has a simple ferromagnetic structure and only one kind of Mn atomic site, the investigations on the origin of the large MA energy will be an interesting research subject as one of the Mn-based alloy systems.…”
Section: Substrate Heating Temperature Effects On the Magnetic Properties Of Mnalge Filmmentioning
confidence: 99%
“…However, the anisotropy direction of transition metal and rare earth based spin pumping are coupled to the crystal field anisotropy direction and orbital moment direction, respectively [36]. Furthermore, the hyperfine-interaction-induced quadrupole anisotropy (of the neglected I term) may contribute to the observed large magnetic anisotropy of manganese alloys [37].…”
Section: Anisotropic Hyperfine Interaction Between Nuclear and Conduc...mentioning
confidence: 99%